Responsivitas Pegawai dalam Meningkatkan Pelayanan Publik di Kantor Kelurahan Mawar Kota Banjarmasin: Penelitian - Siti Fatimah; Junaidy; Fakhsiannor; Sitna Hajar Malawat (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The purpose of this study is to improve the quality of public services, especially in Mawar Village, Banjarmasin City. Responsiveness or responsiveness is the ability of an organization to identify community needs, prioritize needs, and develop them into various service programs. The quality of public services is the core of service performance. Service performance is an important point in the implementation of public services. The quality of public services is an indicator of the success of the public services provided. If the quality of public services is good, then it can be ascertained that the service performance carried out by the service apparatus is also optimal, accompanied by behavior and attitudes that uphold the values ​​of morality and service ethics, and have high responsibility and professionalism in carrying out their duties and responsibilities.